Side-to-side differences in knee laxity and side hop test may predispose an anterior cruciate ligament reinjury in competitive adolescent alpine skiers - Maria Westin; Maria Westin; Lisbeth I. Mirbach; Marita L. Harringe; Marita L. Harringe (Frontiers Media S.A., 2022)
An anterior cruciate ligament (ACL) injury is a common, severe injury in alpine skiing, and anterior cruciate ligament reconstruction (ACLR) is frequently performed in competitive alpine skiers younger than 20 years old. To reduce the reinjury rate, both intrinsic and extrinsic risk factors should be examined. The aim of this study was to investigate possible intrinsic risk factors for an ACL reinjury in competitive alpine skiers. A cohort of 384 alpine skiers (191 males/193 females) from the Swedish ski high schools were prospectively followed during their high school years. The students were clinically examined and physically tested prior to each ski season. In addition, the RAND 36-Item health survey 1.0 (SF-36, Copyright 1994 Medical Outcome Trust, distributed by RAND Corporation) and injuries were prospectively registered. Thirty-one of the skiers (five males/26 females) had undergone an ACLR before entering the ski high school. This cohort was analyzed with respect to the occurrence of, and possible risk factors for an ACL reinjury (including ipsilateral and contralateral ACL injuries). Skiers who sustained an ACL reinjury were called the "ACL reinjury group," and those who did not sustain an ACL reinjury were called the "ACL injury group." Notably, 12 of the 31 students (39%), ten female and two male skiers, aged 16.5 (SD 0.5) years, sustained an ACL reinjury during the two first years at the ski high school. In addition, 10 of the 12 ACL reinjuries occurred within 10-23 months from the first injury [m 14.8 (SD4.7)] and two ACL reinjuries occurred at 29 and 47 months, respectively, from the first injury. It is noted that eight of the ACL reinjuries were to the ipsilateral knee and four to the contralateral knee. There were no differences between the groups with respect to muscle flexibility in the lower extremity, Beighton score, and one leg hop for distance or square hop test. Side-to-side differences were found with respect to knee joint laxity, >3 mm, measured with KT-1000 arthrometer (p = 0.02), and the side hop test (p = 0.04). RAND 36-Item health survey did not predict an ACL reinjury. In conclusion, a side-to-side difference in the side hop test and knee joint laxity (KT-1000) may predispose an ACL reinjury in competitive adolescent alpine skiers.